Role of hypoxia-inducible factors (HIF) in the maintenance of stemness and malignancy of colorectal cancer. (May 2017) - Vadde, Ramakrishna; Vemula, Sarojamma; Jinka, Rajeswari; Merchant, Neha; Bramhachari, Pallaval Veera; Nagaraju, Ganji Purnachandra
Highlights: HIFs play a significant role in maintaining stemness in cancer stem cells. Cancer stem cells are involved in tumor cell resistance and cancer deterioration. Differentiation and self-renewal properties of stem cells lead to colon cancer. Targeting HIFs might provide a new therapeutic approach for colon cancer. Abstract: Hypoxia is a condition of insufficient tissue oxygenation, which is observed during normal development as well as tumorigenesis and its response at the cellular level is primarily mediated through hypoxia inducible factors (HIFs). HIFs have a significant role in the maintenance of stemness in both stem cells as well as in cancer stem cells (CSC) by acting as transcription factors. The CSCs are proposed to be the driving force of colon tumorigenesis and malignancy. These HIFs play a significant role in a wide range of diseases including colon cancer. HIF's signaling functions with stemness, and maintaining Wnt/β-catenin signaling pathways. Due to HIFs functional significance in stemness maintenance in malignancy, targeting HIFs might provide a new approach for development of new therapy for colon cancer. In this review, we will be briefing on the colon and its stem cells, various molecular signaling pathways involved in stemness preservation, and the role hypoxia and its HIFs in the maintenance of stemness in colon stem cells and colon cancer stem cells.